A Case of Myasthenia Gravis Associated With Kaposi Sarcoma. Issue 2 (May 2015) - Peköz, Taylan; Evlice, Ahmet; Koc, Filiz
Abstract : Kaposi sarcoma (KSs) is a slowly progressive systemic multicentric tumor, which affects the skin. KSs may also occur in patients receiving immunosuppressive treatment regimens. A 46-year-old woman was evaluated for skin rash at lower extremities. She was diagnosed as myasthenia gravis associated with thymoma and was receiving a combined pyridostigmine-corticosteroid therapy. Skin biopsy was evaluated in favor of KS. Myasthenia gravis along with KS rarely come across in patients; therefore, the case was evaluated in light of the previous medical literature.